2015
DOI: 10.3892/mmr.2015.4224
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-γ inhibits pancreatic cancer cell invasion and metastasis via regulating MMP-2 expression through PTEN

Abstract: Abstract. The invasive and metastatic behavior of pancreatic cancer is associated with a poor prognosis. Therefore, understanding the molecular mechanisms underlying the invasion and metastasis of pancreatic cancer has important application values theoretically and clinically. In previous years, with increasing studies focusing on tumor pathogenesis, it has been revealed that peroxisome proliferator-activated receptor-γ (PPARγ) and phosphatase and tensin homolog (PTEN) are closely associated with the occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The role of PPAR signalling pathway in pancreatic cancer metastasis has been reported in the literature. Li et al 16 have reported that activation of PPARγ can up‐regulate the tumour suppressor gene PTEN, thereby inhibiting the expression of MMP‐2, thus impairing the migration and invasion of pancreatic cancer cell lines. As the PI3K‐Akt signalling pathway is one of the star signalling pathways for extensive researches, its abnormal activation for promoting invasion and metastasis of pancreatic cancer has been confirmed by many studies 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of PPAR signalling pathway in pancreatic cancer metastasis has been reported in the literature. Li et al 16 have reported that activation of PPARγ can up‐regulate the tumour suppressor gene PTEN, thereby inhibiting the expression of MMP‐2, thus impairing the migration and invasion of pancreatic cancer cell lines. As the PI3K‐Akt signalling pathway is one of the star signalling pathways for extensive researches, its abnormal activation for promoting invasion and metastasis of pancreatic cancer has been confirmed by many studies 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we present evidence of a novel regulatory mechanism for MTSS1 stabilization via the canonical tumor suppressor protein PTEN. PTEN expression has been found to be crucial in minimizing the lethality of PDAC through regulation of the PI3K/AKT pathway [22] ; however, its role in PDAC metastasis has only been briefly studied [23] , [24] , [25] . In this manuscript, we demonstrate that loss of PTEN in PDAC cells not only leads to a more invasive and migratory phenotype, but also results in decreased in MTSS1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PPARγ activation might be beneficial in TNBC therapy. Rosiglitazone, one of the thiazolidinediones, can inhibit metastasis in a murine model of hepatocellular carcinoma [ 31 ] and inhibit pancreatic cancer cell invasion and metastasis by regulating MMP-2 expression through phosphatase and tensin homolog (PTEN) [ 32 ]. There is also growing evidence that PPARγ agonist pioglitazone can inhibit NF-κB activation in cisplatin nephrotoxicity by reducing p65 acetylation via the AMPK-SIRT1/p300 pathway [ 33 ].…”
Section: Discussionmentioning
confidence: 99%